Analisa Pengaruh Jarak Sudu Terhadap Putaran Turbin Ulir Pada Pembangkit Listrik Tenaga Mikro Hidro - Ardika, I Kadek; Weking, Antonius Ibi; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi Elektro, 2019)
S crew Turbine is a turbine that has just been studied. The working principle of this turbine screw is based on a screw pump system which functions to lift water from the river to the surface. The turbine screw is basically the return of the screw pump. To obtain an experimental study of the maximum output produced by a PLTMH using a turbine screw, the research is very difficult to apply in real conditions, and problems with screw turbines are made about the effect of blade distance (10 cm, 12 cm and 15 cm) on efficiency, voltage, current and power on the MHP using a screw turbine. Therefore the research will use a screw turbine prototype on a laboratory with micro power plants. In this study the best measurement at a distance of 21 cm blade with an angle of 280, where the voltage, current, and output power generated by the generator is 129.4 Volts loaded with 60 Watt, No load 162.7 Volts, the current generated is 0.1774 Ampere and the power produced is 22.9 Watts. For generator rotation speed that is equal to 7054 rpm, while turbine rotation speed generated at pressure is equal to 589 rpm before coupling with generator and 318 rpm after coupling with generator, the efficiency obtained in this PLTMH modeling test is at a distance of 22 cm blade with angle slope 280 that is equal to 24.5%.